What influences the course major decision of accounting and non-accounting students? - Owusu, G.M.Y.; Bekoe, R.A.; Okyere, S.A.; Welbeck, E.E. (Journal of International Education in Business, 2019)
Purpose The purpose of this study is to investigate the factors that influence the course major decisions of accounting and non-accounting students. Design/methodology/approach A set of questionnaires was developed and administered to 550 undergraduate business students from the University of Ghana Business School. Statistical tests were conducted to examine the mean differences of students’ views on the factors that influence course major selection. Logistic regression analysis was employed to investigate the factors that influence the course major selection of students. Findings The results demonstrate that students’ confidence in their academic strength and abilities to manage academic work are good predictors of their course major decisions. Also, students who major in accounting are driven more by self-interest, while non-accounting students are largely motivated by extrinsic interest. Moreover, students’ academic performances were found to be influential on their course major decisions. Research limitations/implications This study relied on the views of students from only one university in Ghana, which, in some respect, limits the extent of generalization of the findings. Practical implications The paper provides some useful insights into the factors that inspire students to major in accounting. As a means of addressing the supply deficit of accountants globally, policymakers should find the results useful in developing the appropriate strategy that will attract students to the accounting field. Originality/value The study provides new insights into the course major selection discourse from a developing-country perspective.
Keywords: Accountants; Self-efficacy; Logistic regression; Social cognitive career theory; Course major